The first record of pear psylla Cacopsylla bidens (Hemiptera: Psyllidae) from India along with notes on seasonal occurrence and some elements of its biology. (2nd January 2018) - Akbar, Shahid Ali; Dar, Mudasir Ahmad; Mahendiran, G.; Wachkoo, Aijaz Ahmad
Abstract: Cacopsylla bidens (Šulc, 1907 ) is reported for the first time from India. A brief diagnosis, images and comparison with allied species are provided to validate this new faunal record and facilitate its prompt identification. Seasonality and some elements of the biology of the pest from the Kashmir valley are also provided.